Laser powder bed fusion of eutectic Al–Ni alloys: Experimental and phase-field studies - Boussinot, G.; Döring, Markus; Hemes, S.; Stryzhyboroda, O.; Apel, M.; Schmidt, Michael (Materials and Design, 2021)
Eutectic alloys offer great promises for additive manufacturing owing to an enhancement of mechanical properties due to ultra-fine eutectic microstructures. We study experimentally and numerically through phase-field simulations the Laser Powder-Bed Fusion processing of several near-eutectic Al–Ni alloys. The large variations of cooling rate within the melt pool allow us to investigate the dependence of the selected microstructure on the concentration of the alloy and the solidification velocity. We find that the coupled zone, i.e. the temperature-dependent concentration interval within which the two-phase eutectic coupled growth takes place, drifts towards higher concentrations when the solidification velocity increases. The phase-field simulations essentially support the experimental observations.
CRIS-Team Scopus Importer:2020-11-27
Keywords: Coupled zone; Phase-field simulations; Selective laser melting; Ultra-fine eutectics